Sequential above- and belowground herbivory modifies plant responses depending on herbivore identity. Issue 1 (December 2017) - Kafle, Dinesh; Hänel, Anne; Lortzing, Tobias; Steppuhn, Anke; Wurst, Susanne
Abstract Background Herbivore-induced changes in plant traits can cause indirect interactions between spatially and/or temporally separated herbivores that share the same host plant. Feeding modes of the herbivores is one of the major factors that influence the outcome of such interactions. Here, we tested whether the effects of transient aboveground herbivory for seven days by herbivores of different feeding guilds on tomato plants (Solanum lycopersicum ) alters their interaction with spatially as well as temporally separated belowground herbivores. Results The transient aboveground herbivory by both chewing caterpillars (Spodoptera exigua ) and sucking aphids (Myzus persicae ) had significant impacts on plant traits such as plant growth, resource allocation and phytohormone contents. While the changes in plant traits did not affect the overall performance of the root-knot nematodes (Meloidogyne incognita ) in terms of total number of galls, we found that the consequences of aboveground herbivory for the plants can be altered by the subsequent nematode herbivory. For example, plants that had hosted aphids showed compensatory growth when they were later challenged by nematodes, which was not apparent in plants that had hosted only aphids. In contrast, plants that had been fed byS. exigua larvae did not show such compensatory growth even when challenged by nematodes. Conclusion The results suggest that the earlier aboveground herbivory can modify plant responses to subsequent herbivores, and such modifications may depend upon identity and/or feeding modes of the aboveground herbivores.